1988
DOI: 10.1002/neu.480190602
|View full text |Cite
|
Sign up to set email alerts
|

Activation of DUM cell interneurons by ventral giant interneurons in the cockroach, periplaneta americana

Abstract: Dorsal unpaired median (DUM) cells in orthopteran insects are known to contain the neuromodulatory substance octopamine, and DUM cells with peripheral axons augment synaptic activity at neuromuscular junctions. One of the most studied systems in the cockroach is the giant interneuron (GI) system which controls the initial movements of a wind-mediated escape response. Our data demonstrate that DUM cells that are restricted to the central nervous system (DUM interneurons) receive inputs from ventral giant intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Although not conclusive, this investigation pointed to a possible direct and indirect connection of DUM cells with ascending interneurons of the abdominal cord. Pollack et al (1988) could not reveal any direct connection of DUMa type neurons in cockroach thoracic ganglia to giant interneurons transmitting cercal sensory information through the ventral nerve cord. These findings are compatible with an information transfer from the cerci to thoracic interneurons exciting the DUM cells.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although not conclusive, this investigation pointed to a possible direct and indirect connection of DUM cells with ascending interneurons of the abdominal cord. Pollack et al (1988) could not reveal any direct connection of DUMa type neurons in cockroach thoracic ganglia to giant interneurons transmitting cercal sensory information through the ventral nerve cord. These findings are compatible with an information transfer from the cerci to thoracic interneurons exciting the DUM cells.…”
Section: Discussionmentioning
confidence: 95%
“…Although it is not known whether or not the DUMc neurons we recorded from really contain and secrete octopamine, their behavioral role could depend on a comparable mechanism. Pollack et al (1988) also discuss a modulation of central synapses by local DUM neurons in the cockroach. Similar intraganglionic DUM cells, which lack any peripheral axons, possess relatively small somata and do not generate action potentials, have been demonstrated by Goodman et al (1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This long latency response indicates that the wind sensory input is most probably not conveyed directly to the OA neurons in the thorax but may be conveyed through a polysynaptic connection via the brain. In support of this, Pollack et al (1988) showed that the GIs probably do not synapse directly onto the efferent OA neurons. Moreover, removing the brain nearly completely abolished the robust response of the OA neurons to wind.…”
Section: Evoked Responses Of the Oa Neuronsmentioning
confidence: 84%